Absolutnie wolny? Wolność człowieka w filozofii Giovanniego Pico Della Mirandoli - Nowakowski, Dawid (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2011)
Pico was generally perceived as a representative of the Pelagian heresy and a supporter of absolute freedom of man. However, more detailed analysis of his works reveals that in his views he was much more traditional than it used to be judged. Although Pico does not negate human freedom, he has consistently stressed the necessity of grace in salvation. So, in the question of free will Pico represents traditional post-Augustinian school and advocates, also present at the Thomas’, graduated concept of grace.